2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psychological Safety on the Interaction of Students in Teams

Abstract: and involved in research in service learning, assessment processes and interventions aimed at improving learning objective attainment. Prior to his University assignments he was the Founder and CEO of The EDI Group, Ltd. and The EDI Group Canada, Ltd, independent professional services companies specializing in B2B electronic commerce and electronic data interchange. The EDI Group companies conducted syndicated market research, offered educational seminars and conferences and published The Journal of Electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Newer research has started to explore the concept of psychological safety in terms of teaming [11][12][13][14]. One study found that teams with members who felt psychologically safe had better outcomes [2]. The level of psychological safety in a team may also be indicative of the levels of conflict, cohesion and satisfaction in teams [12].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer research has started to explore the concept of psychological safety in terms of teaming [11][12][13][14]. One study found that teams with members who felt psychologically safe had better outcomes [2]. The level of psychological safety in a team may also be indicative of the levels of conflict, cohesion and satisfaction in teams [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this work-in-progress paper, we perform a more focused study of two student teaming aspects that have been shown to vary for students from different backgrounds: (a) roles that students play on their project teams [1], and (b) their psychological safety. [2] Our research questions are: (1) How are the roles on student-led project teams chosen or assigned? (2) How do engineering project teams foster psychological safety for diverse members?…”
Section: Introductionmentioning
confidence: 99%
“…• Communication: members provide and receive information objectively • Coordination: balancing workloads among members in order to work effectively • Cooperation: working together and helping one another • Composition: members reflect on/respond to their team's strengths and weaknesses • Conflict: conflict is addressed and mitigated constructively • Creativity: members share ideas and generate more ideas together • Cohesiveness: group pride in working toward a common goal CATME peer evaluation surveys have also been used in the past to measure students' perceptions of teamwork, including their views of psychological safety [9]. More information on how CATME collects these views is listed in the Methods section of this paper.…”
Section: Study Intent and Supporting Literaturementioning
confidence: 99%
“…More information on how CATME collects these views is listed in the Methods section of this paper. The questions also reflect the role of trust among team members, where psychological safety appears to be a manifestation of trust [9].…”
Section: Study Intent and Supporting Literaturementioning
confidence: 99%
“…Disagreement or conflict generally fell into three categories-task, process, and relationship-all of which were considered in this study. Part Three probed psychological safety, i.e., how comfortable students felt about working in their teams, through validated survey questions (Beigpourian et al 2020). Part Four asked questions about engineering identity drawn from the work of Hazari et al (2010), Godwin (2016), and Tonso (2006b.…”
Section: Data Collectionmentioning
confidence: 99%